Study on performance improvement methods of energy-harvesting control valves for energy supply in marine intelligent pipeline networks - Guangchao Zhang; Shinong Wang; Jinmin Xiong; Yudong Xie; Yong Wang (Frontiers in Marine Science, 2026)
To ensure timely valve response in the event of leaks in marine oil and gas pipeline networks—thereby minimizing the impact of such leaks on the marine ecosystem—providing a continuous and stable power supply for pipeline networks in offshore environments remains a challenge. Integrating a runner into the valve cavity of a control valve to capture fluid energy flowing through the valve for power generation is a promising solution. However, current studies fail to emphasize the impact of valve body structure—and this research status of “prioritizing runners over valve bodies” while neglecting the coupling effect has become a major bottleneck for the further advancement of control valve-based hydroelectric technology. Based on the concept of shape-property collaboration, this study, through the bidirectional drive of shape optimization and performance improvement, fully considers the coupling characteristics of the runner and valve, modifies the geometric configuration of the valve cavity, and enhances the performance of the energy-harvesting valve. Based on an experimentally validated CFD model, the study reveals the influence laws of valve opening and the characteristic parameters of the new valve cavity configuration (flow-collecting deflection angle and surface grooves) on the valve’s fluid regulation performance and energy-harvesting characteristics. The results show that the flow-collecting structure and surface groove structure of the valve cavity have a significant effect on improving the performance of the energy-harvesting control valve.